2014
DOI: 10.1111/ajo.12190
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy in obstetrics and gynaecology: The trainees' perspective

Abstract: Trainees perceive limitations in their anatomical knowledge. A formalised RANZCOG anatomy course would be of value in providing structured education and assessment of trainees' knowledge and establishing whether there are improvements in surgical competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…While 21.2% and 6.9% of first-year and fifth-year trainees, respectively, rated their overall anatomy knowledge as either very poor or poor, 9.6% of first-year trainees and 62% of fifth-year rated their knowledge as either good or very good. Similar trends in overall surgical anatomy knowledge were shown by Sgroi et al [6] where 11% of O&G resident doctors reported their surgical anatomical knowledge as adequate at the beginning of training, and 77% reported adequate knowledge by the final year of training. In addition, final year residents were more able to identify structures compared to firstyear residents.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While 21.2% and 6.9% of first-year and fifth-year trainees, respectively, rated their overall anatomy knowledge as either very poor or poor, 9.6% of first-year trainees and 62% of fifth-year rated their knowledge as either good or very good. Similar trends in overall surgical anatomy knowledge were shown by Sgroi et al [6] where 11% of O&G resident doctors reported their surgical anatomical knowledge as adequate at the beginning of training, and 77% reported adequate knowledge by the final year of training. In addition, final year residents were more able to identify structures compared to firstyear residents.…”
Section: Discussionsupporting
confidence: 81%
“…The results of our study showed that trainees who attended and/or performed surgical procedures more often rated their surgical anatomy knowledge higher. Another report showed that the surgical anatomy knowledge of resident doctors was related to the number of procedures they performed as primary surgeons [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With working hour restrictions, lack of protected training time, and merciless struggle for operating time amongst trainees, the bulk of these preparations needs to be done outside of working hours and the OR. A simple initial step would be to develop a solid grasp of surgical anatomy through textbooks or focused workshops [22]; indeed, a recent survey of Australian O&G trainees revealed a clear dearth of structured anatomy curricula in the training program [23]. Further, regular review of laparoscopic videos, either open-source or those manually recorded, has also been shown to be useful for skill acquisition amongst gynaecologic residents, particularly in junior learners [24].…”
Section: Will Prepare and Someday My Chance Will Comementioning
confidence: 99%
“…These have resulted in a reduction in the number of abdominal and vaginal hysterectomies a resident performs per year [1,2]. Other factors affecting surgical training are the reduced time available for attending teaching [3], reduction and restrictions in resident duty hours [4], impact of electronic medical records [5], inadequate teaching and understanding of anatomy [6], and financial impact of teaching in the operating room [7]. Evidence for the inadequacies of recent graduates is found in a recent survey of 130 Ob-Gyn fellowship directors who reported only 20% of first-year fellows were able to independently perform a vaginal hysterectomy, and 46% were able to independently perform an abdominal hysterectomy [8].…”
mentioning
confidence: 99%